Mechanoadaptation of the bones of mice with high fat diet induced obesity in response to cyclical loading. (19th July 2021) - Eller, Kerry; DiMauro, Nicole; Garnier, Julien; Ruberti, Anika; Meslier, Quentin; Piet, Judith; Shefelbine, Sandra J.
Abstract: An upward trend in childhood obesity implies a great need to determine its effects, both immediate and long-term. Obesity is osteoprotective in adults, but we know very little about the effects of obesity on the growing skeleton, particularly its ability to adapt to load. The objective of this research is to assess bone mechanoadaptation in adolescent obese mice. Ten mice were fed a high-fat diet (HFD) from 4 to 16 weeks of age, while a control group of the same size received a normal diet (ND). At 14 weeks of age, right tibiae were cyclically loaded with a 12 N peak load for HFD mice and a 9 N peak load for ND mice three times a week for two weeks, resulting in equal peak strains of about 2500 microstrain. At 16 weeks of age, mice were sacrificed, and tibiae and gonadal fat pads were dissected. Fat pads were weighed as an obesity indicator, and tibiae were imaged with microCT to measure bone structure. The left tibiae (nonloaded) were subsequently decalcified, stained with osmium, and scanned to quantify marrow fat. Results showed that HFD mice had larger tibial cross-sectional areas compared to ND mice, as well as greater marrow adiposity. However, there was no significant difference in the amount of bone adaptation in the cortical or trabecular bone between the two groups. This indicates that the bones of HFD and ND mice adapt equally well to loading.